2019
DOI: 10.3390/nano9040626
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of ZnTe:Cu Back Contact on the Performance of CdTe Nanocrystal Solar Cells with Inverted Structure

Abstract: CdTe nanocrystal (NC) solar cells have received much attention in recent years due to their low cost and environmentally friendly fabrication process. Nowadays, the back contact is still the key issue for further improving device performance. It is well known that, in the case of CdTe thin-film solar cells prepared with the close-spaced sublimation (CSS) method, Cu-doped CdTe can drastically decrease the series resistance of CdTe solar cells and result in high device performance. However, there are still few r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…16(a) together with the energy band diagram using a 20 nm ZnTe:Cu back contact annealed at 200 1C, and the device yielded a PCE of 6.38%. 215 Given that a low resistive back contact is needed to fabricate high-efficiency devices, to well match the interfacial properties of ZnTe, a heavily doped p-type Cu 1.4 Te, ZnTe/Cu 1.4 Te alloyed bilayer was synthesized for application in a device with the architecture of glass/FTO/SnO 2 /CdS/CdTe/ZnTe/Cu 1.4 Te/Au, as shown in Fig. 17 with its energy band diagram.…”
Section: View Article Onlinementioning
confidence: 99%
See 1 more Smart Citation
“…16(a) together with the energy band diagram using a 20 nm ZnTe:Cu back contact annealed at 200 1C, and the device yielded a PCE of 6.38%. 215 Given that a low resistive back contact is needed to fabricate high-efficiency devices, to well match the interfacial properties of ZnTe, a heavily doped p-type Cu 1.4 Te, ZnTe/Cu 1.4 Te alloyed bilayer was synthesized for application in a device with the architecture of glass/FTO/SnO 2 /CdS/CdTe/ZnTe/Cu 1.4 Te/Au, as shown in Fig. 17 with its energy band diagram.…”
Section: View Article Onlinementioning
confidence: 99%
“…16(a) together with the energy band diagram using a 20 nm ZnTe:Cu back contact annealed at 200 °C, and the device yielded a PCE of 6.38%. 215…”
Section: Critical Insights Into the Role Of Znte Layers In Cdte Thin ...mentioning
confidence: 99%
“…Amin et al (2002) 76 tried ZnTe and Cd 0.5 Zn 0.5 Te:N back contacts to thin (1 µm CdTe) solar cells obtaining 8.3% PCE (low FF of 49%) for ZnTe/C:Cu/Ag contacted devices. Chen et al (2019) 77 studied ZnTe:Cu back contacts to CdTe using a CdSe buffer layer (ITO/ZnO/CdSe/CdTe/ZnTe:Cu/Au structure). Although an improvement over the Au only back contact was observed, the maximum PCE was 6.38%.…”
Section: Zinc Telluridementioning
confidence: 99%
“…It is well known that Cu-doped interface layer has been applied successfully to CdTe thin film solar cells prepared by close-space sublimation (CSS) method [ 11 , 12 ]. Unfortunately, fabricating a homogeneous Cu-doped layer on CdTe NC thin films remains a challenge, since Cu may diffuse quickly along the crystal boundaries of NCs and restrict further device performance improvement [ 13 ]. Yang et al [ 14 ] investigated the application of commercially available poly-[3-(potassium-6-hexanoate)thiophene-2, 5-diy] (P3KT) as a HTL for aqueous processed CdTe NC solar cells with the configuration of ITO/SnO 2 /CdS/CdTe/P3KT/MoOx/Au and found that the insertion of P3KT optimized bandgap alignment and enhanced carrier collection efficiency.…”
Section: Introductionmentioning
confidence: 99%